India : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper paints a picture of the Indian economy that has made great strides, but has more to do to accelerate growth and reduce poverty. The paper assesses empirically whether India has entered a new phase of higher trend growth. Two alternative methodologies are used to disentangle underlying structural growth trends from shorter-term cyclical fluctuations around this trend. The paper focuses on a number of the reforms required to ensure that needed high growth can be achieved on a sustained basis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet